Value Distribution of Meromorphic Functions - Zheng, Jianhua; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
"Value Distribution of Meromorphic Functions" focuses on functions meromorphic in an angle or on the complex plane, T directions, deficient values, singular values, potential theory in value distribution and the proof of the celebrated Nevanlinna conjecture. The book introduces various characteristics of meromorphic functions and their connections, several aspects of new singular directions, new results on estimates of the number of deficient values, new results on singular values and behaviours of subharmonic functions which are the foundation for further discussion on the proof of the Nevanlinna conjecture. The independent significance of normality of subharmonic function family is emphasized. This book is designed for scientists, engineers and post graduated students engaged in Complex Analysis and Meromorphic Functions. Dr. Jianhua Zheng is a Professor at the Department of Mathematical Sciences, Tsinghua University, China.
Preliminaries of Real Functions -- Characteristics of a Meromorphic Function -- T Directions of a Meromorphic Function -- Argument Distribution and Deficient Values -- Meromorphic Functions With Radially Distributed Values -- Singular Values of Meromorphic Functions -- The Potential Theory in Value Distribution.
Keywords: Mathematics; Global analysis (Mathematics).; Functions of complex variables; Mathematics; Analysis; Functions of a Complex Variable; Real Functions